Bacterial Resistance to Leucyl-tRNA Synthetase Inhibitor GSK2251052 Develops during Treatment of Complicated Urinary Tract Infections - O'Dwyer, Karen; Spivak, Aaron T.; Ingraham, Karen; Min, Sharon; Holmes, David J.; Jakielaszek, Charles; Rittenhouse, Stephen; Kwan, Alan L.; Livi, George P.; Sathe, Ganesh; Thomas, Elizabeth; Van Horn, Stephanie; et al. (Antimicrobial agents and chemotherapy, 2015)
GSK2251052, a novel leucyl-tRNA synthetase (LeuRS) inhibitor, was in development for the treatment of infections caused by multidrug-resistant Gram-negative pathogens. In a phase II study (study LRS114688) evaluating the efficacy of GSK2251052 in complicated urinary tract infections, resistance developed very rapidly in 3 of 14 subjects enrolled, with ≥32-fold increases in the GSK2251052 MIC of the infecting pathogen being detected. A fourth subject did not exhibit the development of resistance in the baseline pathogen but posttherapy did present with a different pathogen resistant to GSK2251052. Whole-genome DNA sequencing of Escherichia coli isolates collected longitudinally from two study LRS114688 subjects confirmed that GSK2251052 resistance was due to specific mutations, selected on the first day of therapy, in the LeuRS editing domain. Phylogenetic analysis strongly suggested that resistant Escherichia coli isolates resulted from clonal expansion of baseline susceptible strains. This resistance development likely resulted from the confluence of multiple factors, of which only some can be assessed preclinically. Our study shows the challenges of developing antibiotics and the importance of clinical studies to evaluate their effect on disease pathogenesis. (These studies have been registered at ClinicalTrials.gov under registration no. NCT01381549 for the study of complicated urinary tract infections and registration no. NCT01381562 for the study of complicated intra-abdominal infections.)